Prognostic significance of alpha frequency EEG rhythm in coma after cardiac arrest. Issue 9 (September 1978) - Sørensen, K; Thomassen, A; Wernberg, M
Abstract : Sixty-five patients who remained in coma for more than 24 hours after resuscitation from cardiac arrest were divided into two groups according to their EEGs. Thirteen patients were found to have rhythm of alpha frequency while 52 had the usual EEG findings after cerebral anoxia. Three patients from the group with alpha frequency EEG rhythms regained full consciousness but showed severe sequelae. Our results suggest that the prognosis of comatose patients with EEG rhythm of alpha frequency is no poorer than that of other individuals who are comatose after cardiac arrest.